Optimization of convective drying assisted by ultrasound for Mango Tommy (Mangifera indica L.) (2018)
Convective drying is a conventional method to prolong the shelf-life of foods that could negatively affect the product quality due to the long exposure time to high temperature. Ultrasound (US) has been used for reducing the drying time while maintaining the product quality. In this study a Box-Behnken design of Response Surface Methodology (RSM) was used to evaluate the effects of US time-frequency (t), US power level (Pot), and hot air temperature (T) on the drying process time (DPT), apparent density (AD), and color difference (ΔE) of the dried mango slices (10.0 ± 1.0% wet basis). Fisher's statistical testing was performed for the analysis of variance (ANOVA) for quadratic regression equations. The optimization goals were to minimize the responses. Modeled optimized conditions were 52–55 °C, 45–60 W, and 3 min/30 min for T, Pot, and t, respectively. Energy consumption and carbon footprint were also estimated during the validation of the optimal drying conditions. Practical applications: This research explored the use of response surface methodology polynomial models fitted to the experimental data of US assisted drying assays to find the best values of air temperature, time-frequency, and power of sonication for minimization of the drying process time (DPT) apparent density, and color difference of mango slices. The results specified ranges for the input-variables where lower DPT and properly dried mango quality parameters co-exist with important reductions in operational costs and carbon foot-print compared with those estimated for conventional dehydration process. These findings are of interest toward the development of greener and more sustainable food drying processes. © 2017 Wiley Periodicals, Inc.